The Great Lakes Silviculture Library: Insights into a Case Study Platform. Issue 3 (16th December 2021) - Moser, Robert Lane; Sagor, Eli S; Russell, Matthew B; Windmuller-Campione, Marcella A
Abstract: Innovation and knowledge exchange are critical to foster adaptive management and continual learning. Across the spectrum of knowledge exchange, ranging from peer-reviewed research to anecdotes, there is a largely untapped middle ground: real-world silvicultural case studies implemented and documented by foresters. The University of Minnesota Great Lakes Silviculture Library is a novel, freely available platform designed to enable foresters to exchange these case studies. Five years after its launch, we conducted focus groups with foresters from Minnesota and Wisconsin, USA, and Ontario, Canada, to explore the platform's usage and value. Participants valued having access to examples of silvicultural treatments and their outcomes that they could easily digest, apply, and share. They gained new knowledge from management across administrative boundaries. They also appreciated the consistent, relatable case study format. However, participants noted that limited time was the primary barrier to wider authorship and readership. The Library enables information exchange across agencies and disciplines within natural resources, giving greater voice to practicing foresters and supplementing other sources of forestry knowledge.